What is the term to term rule: 1, -6, -13, -20, -27, -34

Question

What is the term to term rule: 1, -6, -13, -20, -27, -34

in progress 0
Quinn 3 days 2021-09-14T00:04:52+00:00 2 Answers 0

Answers ( )

    0
    2021-09-14T00:06:10+00:00

    Answer:

    Step-by-step explanation:

    Term 2 – term 1 = -6 – 1 = -7

    Difference = -7

    Tn = a + (n-1)d

        = 1 + (n-1)*(-7)

       = 1 -7n + 7

     = 8 – 7n

    0
    2021-09-14T00:06:36+00:00

    Answer:

    The term-to-term rule for the sequence 1, -6, -13, -20, -27, -34 is…

    YOU TAKE AWAY 7 TO GET THE NEXT NUMBER!

    Step-by-step explanation:

    i.e. 1 – 7 = -6, -6 – 7 = -13 and so on…

    In other words, the formula is -7n+8

    HOPE THIS HELPS!

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )